Japanese Encephalitis: A Clinical Review - Haque, Md Azizul; Chowdhury, Fazle Rabbi; Islam, Md Nurul; Kabir , Habiba; Ahasan, HAM Nazmul (Journal of Medicine, 2025)
Japanese encephalitis (JE) is a severe disease caused by the Japanese encephalitis virus of the genus Flavivirus and the family Flaviviridae. Mosquitoes of the Culex Vishnu subgroup, particularly Culex tritaeniorhynchus, are the main vectors of JEV. This zoophilic mosquito species is sustained in an enzootic cycle with pigs and wading birds as amplifying hosts. JE is endemic to rural Asia, the Western Pacific, and northern Australia, with three billion people at risk. Globally, an estimated 68,000 clinical cases occur annually, and over 13,000 deaths. Most JEV infections are subclinical; symptomatic infection can cause a spectrum of clinical manifestations ranging from undifferentiated febrile illness and aseptic meningitis to acute encephalitis. One-third of JE infections are fatal, and half of the survivors develop permanent neurological sequelae. Because of the frequent neurological sequelae of the condition, JEV causes loss of more disability-adjusted life years than any other arthropod-borne virus. WHO recommends incorporating the JE vaccine into the routine childhood immunization program in all JE-endemic areas. However, not all JEV-affected countries, including Bangladesh, have the vaccine implemented in their routine immunization programs. Introducing a childhood vaccination program can significantly reduce the number of JE cases in Bangladesh. J MEDICINE 2025; 26: 48-55